GAMBARAN PERSEPSI TERHADAP DUKUNGAN SOSIAL PADA REMAJA YANG MENGALAMI KEHAMILAN DI LUAR NIKAH (STUDI KASUS DI YAYASAN R) - Chrishianie Chrishianie; Venie Viktoria Rondang M (MANASA, 2014)
Unwanted pregnancy before marriage bring complex problems, especiallyfor adolescents who experience the pregnancy. Pregnancy as a relatively newexperience, accompanied by any change in the physiological, psychological, andthe role that occur rapidly, can be a stressor in adolescents in that situation.Otherwise, most teenagers who become pregnant does not have a partner,whereas the presence and support partner is an important factor for pregnantwomen. Instead, these teenagers will seek support from other sources. RFoundation specifically provides services for women who become pregnant outside of marriage. The support provided by the R Foundation is expected to facilitate the youth to live with a stressful pregnancy. The purpose of this study is to describe the perceptions of social support in adolescents who experience unwanted pregnancy before marriage. In accordance with the purpose of the research, this study used a qualitative approach. The method for collecting the data were interviews. The number of subjects in this study consisted of two subject aged 18 and 17 years old. Thematic analysis is implemented for analyzing interviews data. The results showed that the four aspects of social support to help teens in carrying out illegitimate pregnancy. Same perception of the companionship and emotional support/esteem support is considered dominant in helping these young people cope with the psychological stress due to unwanted pregnancy before marriage. Tangible/instrumental support can facilitate the needs of youth to support the pregnancy. Informational provide knowledge about pregnancy, as well as planning for the future of youth and her future.